2016
DOI: 10.1002/srin.201600399
|View full text |Cite
|
Sign up to set email alerts
|

Study on Slopping Prevention in the BOF Steelmaking Process

Abstract: A new method of preventing slopping is proposed in this paper, by simply blowing gas at the top of the foam surface. The physical experiment results show that the foam height can be effectively decreased by the top blowing air. The maximum decrease of the foam height can reach around 70 mm with an initial foam height of 145 mm in the current setup, around a 48% decrease. The first 40 mm of the foam height is easy to destroy with a low flow rate from the top. However, it is increasingly difficult for a further … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…In the experiments conducted by Ni et al (3) and Wang et al (4) , silicon oil with a viscosity comparable to that of converter slag was used as the simulated slag. However, in this experiment, which was conducted on a larger scale than Ni et al's 3) apparatus (cylindrical shape with the diameter of 93 mm and the height of 280 mm), generating a large number of fine bubbles to foam silicon oil was impractical.…”
Section: Experimental Methods 1 Water Model Experimentsmentioning
confidence: 99%
See 3 more Smart Citations
“…In the experiments conducted by Ni et al (3) and Wang et al (4) , silicon oil with a viscosity comparable to that of converter slag was used as the simulated slag. However, in this experiment, which was conducted on a larger scale than Ni et al's 3) apparatus (cylindrical shape with the diameter of 93 mm and the height of 280 mm), generating a large number of fine bubbles to foam silicon oil was impractical.…”
Section: Experimental Methods 1 Water Model Experimentsmentioning
confidence: 99%
“…In the experiments investigating the influence of the number of nozzle holes, nozzle tips with four to six holes were used. Even when the number of nozzle holes was the same, the jet intensity varied depending on the nozzle diameter, leading to different effects on foaming 3) . Therefore, the nozzle tips were designed based on an index related to the jet intensity to ensure consistency in this index, and the influence of the number of nozzle holes was investigated under these conditions.…”
Section: Experimental Methods 1 Water Model Experimentsmentioning
confidence: 99%
See 2 more Smart Citations
“…As a result, it is inferred that this reduction in the maximum height of the silicone oil foam was caused by the destruction of the top blowing jet by the foam structure. Ni et al [28] also indicated that top blowing inert gas can suppress slag foaming. However, it should be mentioned that the compressed air used in this work is nonreactive, which is inconsistent with the top blowing oxygen of BOF steelmaking in practice.…”
Section: Analysis Of Splashing Mechanismmentioning
confidence: 99%